Natural history of Helicobacter pylori VacA toxin in human gastric epithelium in vivo: vacuoles and beyond. Issue 1 (December 2017) - Necchi, Vittorio; Sommi, Patrizia; Vanoli, Alessandro; Fiocca, Roberto; Ricci, Vittorio; Solcia, Enrico
Abstract Uptake, intracellular trafficking and pathologic effects of VacA toxin fromHelicobacter pylori have been widely investigatedin vitro . However, no systematic analysis investigated VacA intracellular distribution and fate inH. pylori -infected human gastric epitheliumin vivo, using ultrastructural immunocytochemistry that combines precise toxin localization with analysis of the overall cell ultrastructure and intercompartimental/interorganellar relationships. By immunogold procedure, in this study we investigated gastric biopsies taken from dyspeptic patients to characterize the overall toxin's journey inside human gastric epithelial cellsin vivo . Endocytic pits were found to take up VacA at sites of bacterial adhesion, leading to a population of peripheral endosomes, which in deeper (juxtanuclear) cytoplasm enlarged and fused each other to form large VacA-containing vacuoles (VCVs). These directly opened into endoplasmic reticulum (ER) cisternae, which in turn enveloped mitochondria and contacted the Golgi apparatus. In all such organelles we found toxin molecules, often coupled with structural damage. These findings suggest direct toxin transfer from VCVs to other target organelles such as ER/Golgi and mitochondria. VacA-induced cytotoxic changes were associated with the appearance of auto(phago)lysosomes containing VacA, polyubiquitinated proteins, p62/SQSTM1 protein, cathepsin D, damaged mitochondria and bacterial remnants, thus leading to persistent cell accumulation of degradative products.